2005
DOI: 10.1097/01.sap.0000168370.81333.97
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Calcium Hydroxylapatite for Nipple Projection After Failed Nipple-Areolar Reconstruction

Abstract: Numerous studies have shown that the final stage in breast reconstruction, creation of the nipple-areolar complex, correlates highly with patient satisfaction and acceptance of body image. There are many different techniques, including nipple sharing, free-composite grafts, and local "pull-out" flaps, all of which are vulnerable to an unpredictable degree of loss of projection and possible need for reoperation. This leads to problems with symmetry and overbuilding the initial reconstruction with wider-based, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Indeed, there is much debate as to the longevity of volume correction offered by this filler. Nevertheless, the product has been successfully used for nipple reconstruction 22 and in patients with human immunodeficiency virus-associated facial lipoatrophy, and has demonstrated efficacy in the correction of concavities and other visible signs of volume loss. 23 It is currently U.S. Food and Drug Volume 118, Number 3S • Volumizing with Poly-L-Lactic Acid Administration approved for oromaxillofacial deficits and, and the manufacturer has filed for wider cosmetic application.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, there is much debate as to the longevity of volume correction offered by this filler. Nevertheless, the product has been successfully used for nipple reconstruction 22 and in patients with human immunodeficiency virus-associated facial lipoatrophy, and has demonstrated efficacy in the correction of concavities and other visible signs of volume loss. 23 It is currently U.S. Food and Drug Volume 118, Number 3S • Volumizing with Poly-L-Lactic Acid Administration approved for oromaxillofacial deficits and, and the manufacturer has filed for wider cosmetic application.…”
Section: Discussionmentioning
confidence: 97%
“…Evans et al 34 used calcium hydroxylapatite gel (Radiesse; BioForm, Inc., Franksville, Wis.) to revise previous nipple-areola reconstructions for six patients with loss of projection. They assessed patient satisfaction over 10 months and reported that all patients were satisfied, with no postoperative complications (Tables 5 and 6).…”
Section: Calcium Hydroxyapatite Gelmentioning
confidence: 99%
“…23 Reported allogeneic materials have included acellular dermal matrix, [24][25][26][27][28][29] bone allograft, 16 and extracellular matrix collagen. 30 Silicone, 31 polyurethane, 32 polytetrafluoroethylene, 33 and calcium hydroxylapatite gel 34 are the synthetic materials described to date for use in nipple augmentation. Combinations of the above materials have also been reported.…”
mentioning
confidence: 99%
“…Studies have shown that the recreation of the nipple has a high correlation with overall patient satisfaction and acceptance of body image, 1 but long-term patient total satisfaction has been reported to be as low as 16%. 2 Thus, it is highly important to the psychological health of the patient that completion of the breast reconstruction by creating a nipple–areola complex that matches the contralateral nipple has a positive aesthetic result.…”
mentioning
confidence: 99%
“…To overcome nipple projection loss with skin flaps alone, many surgeons have advocated the insertion of alloplastic materials, such as calcium hydroxylapatite 1 or polytetrafluoroethylene, 3 or autologous tissue grafts, to act as an internal stent or bolster to support projection. Although autologous techniques, which use rib cartilage, 4 auricular cartilage, 5 dermis, 6,7 or other autologous tissues, 8 generally have been successful, the harvesting of the autologous graft material can lead to increased operative times and greater patient morbidity, including pain and infection.…”
mentioning
confidence: 99%